Preventing heart failure: a position paper of the Heart Failure Association in collaboration with the European Association of Preventive Cardiology. (27th January 2022) - Piepoli, Massimo F.; Adamo, Marianna; Barison, Andrea; Bestetti, Reinaldo B.; Biegus, Jan; Böhm, Michael; Butler, Javed; Carapetis, Jonathan; Ceconi, Claudio; Chioncel, Ovidiu; Coats, Andrew; Crespo‐Leiro, Maria G.; et al.
Abstract: The heart failure epidemic is growing and its prevention, in order to reduce associated hospital readmission rates and its clinical and economic burden, is a key issue in modern cardiovascular medicine. The present position paper aims to provide practical evidence‐based information to support the implementation of effective preventive measures. After reviewing the most common risk factors, an overview of the population attributable risks in different continents is presented, to identify potentially effective opportunities for prevention and to inform preventive strategies. Finally, potential interventions that have been proposed and have been shown to be effective in preventing heart failure are listed.